Pengaruh Ekspektasi Pendapatan, Literasi Keuangan Dan Efikasi Diri Terhadap Minat Berwirausaha Mahasiswa Akuntansi Kota Batam - Laia, Dewiyanti; Husda, Anggun Permata (LPPM Universitas Putera Batam, 2024)
This study aims to analyze the influence of income expectations, financial literacy, and self-efficacy on the entrepreneurial intentions of accounting students. The research method used is multiple linear regression with a sample of 100 accounting students selected used the slovin formula. Data were collected through questionnaires that have been tested of validity and reliability. The results show that income expectations, financial literacy, and self-efficacy significantly affect entrepreneurial intentions. The adjusted R2 value of 0.277 indicates that 27.7% of the variability in entrepreneurial intentions can be exolained by these three independent variables, while the remaining 73.3% is influenced by other variabels not included in this study. The partial t-test results show that all independent variabels have a significant inluence on the dependent variable. The study concludes that to enhance the entrepreneurial intentions of accounting students, there needs that to be an improvement in income expectations, financial literacy, and self-efficacy